2022
DOI: 10.3390/nu14040804
|View full text |Cite
|
Sign up to set email alerts
|

Vitamin D Status and Health Outcomes in School Children in Northern Ireland: Year One Results from the D-VinCHI Study

Abstract: (1) Background: Vitamin D status has never been investigated in children in Northern Ireland (UK). (2) Methods: Children (4–11 years) (n = 47) were recruited from November 2019 to March 2020 onto the cross-sectional study. Anthropometry was assessed. Plasma 25-hydroxyvitamin D (25(OH)D) was analysed. Vitamin D intake, parental knowledge and perceptions, participant habits, physical activity and sedentary behaviour were established via questionnaire. Muscle strength was assessed via isometric grip strength dyna… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

2
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
3

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(9 citation statements)
references
References 77 publications
2
6
0
Order By: Relevance
“…Furthermore, 55⋅5 % of children had a 25(OH)D below 50 nmol/l in winter. This figure is identical (55⋅3 %) to the recent finding in children ( n = 47, age 7–11) living in Northern Ireland between November and March (21) . While the prevalence of deficiency/insufficiency varied by season in the under 12s, the difference was not significant, but is likely explained by the small sample size and lack of statistical power.…”
Section: Discussionsupporting
confidence: 88%
See 1 more Smart Citation
“…Furthermore, 55⋅5 % of children had a 25(OH)D below 50 nmol/l in winter. This figure is identical (55⋅3 %) to the recent finding in children ( n = 47, age 7–11) living in Northern Ireland between November and March (21) . While the prevalence of deficiency/insufficiency varied by season in the under 12s, the difference was not significant, but is likely explained by the small sample size and lack of statistical power.…”
Section: Discussionsupporting
confidence: 88%
“…Due to Irelands' north latitude (53°N), little or no vitamin D can be synthesised during winter months and adult deficiency is prevalent (18,19) . However, studies in Irish children and adolescents are limited, with deficiency (<30 nmol/l) ranging between 5 and 22 % and levels <50 nmol/l reported to be between 27 and 89 % (20)(21)(22)(23) . Factors related to familial socioeconomic status (SES) have been suggested to affect vitamin D including lower diet quality, reduced intake of oily fish and supplement intakes and less access to outdoor amenities (24)(25)(26) .…”
Section: Introductionmentioning
confidence: 99%
“…3 These figures are little lower than the Indian multicentre study of vitamin D status in children and adolescents of 58%. 10 Similarly a study carried out in Karachi Pakistan on children under 5 showed 60% of children are deficient in vitamin D. 11 The study from northern Ireland on school children showed 48.9% insufficiency of vitamin D. 12 Vitamin D level of girls in this study were reported slightly lower 25.88% than boys 25% but severe deficiency less than 10ng/ml was significantly more in girls 4.7% than boys 2.3 %. A study from china also documented low levels of vitamin D (17.86%) in girls than boys 19.2%.…”
Section: Discussionmentioning
confidence: 52%
“…Electronic devices such as video game consoles, portable tablets, computers, and cell phones have provided children with entertainment that can be enjoyed indoors. As a result, they are less likely to engage in outdoor activities, which has significantly decreased exposure to sunlight in this age group [11,14]. Although obesity has also been reported as a risk factor for VDD with various proposed mechanisms of action, a portion of the VDD observed in obese individuals may be a result of confounding effects [15].…”
Section: Epidemiologymentioning
confidence: 99%